A high precision step height measurement system of optical fiber multiplexed interferometry. (January 2015) - Ma, Sen; Xie, Fang; Wang, Yunzhi; Chen, Liang
Highlights: A high precision step height measurement system is proposed. The peak of the low coherence interferogram could be identified precisely. The system is stabilized by a feedback loop for on-line measurement. The measurement range is 6 mm and the measurement resolution is less than 1 nm. Abstract: This paper focuses on obtaining high precision of a stabilized and interleaving high coherence and low coherence interferometric optical fiber system which is capable of the measurement of step height with a symmetric peak-searching method. The interferometer performing the measurement works in both modes of low coherence interferometry and high coherence interferometry simultaneously. The range of the step height is determined by the low coherence interferometric signal while the resolution of the measurement is decided by the high coherence interferometric signal which is also used to compensate for the influences induced by the environmental disturbances through a feedback loop. High addressing precision of the peak of the low coherence interferogram, which influences the measurement precision violently, has been obtained by searching symmetrically the peak from two sides of the low coherence interferogram. The maximum step height that can be measured is 6 mm, while the measurement resolution is less than 1 nm. The standard deviation of 10 times of the measurement results of a gauge block with the height of 1 mm is 0.5 nm.